Stationary Solutions for a Generalized Kadomtsev-Petviashvili Equation in Bounded Domain (Communications in Mathematical Research, 2021)
In this work, we are mainly concerned with the existence of stationarysolutions for a generalized Kadomtsev-Petviashvili equation in bounded domain of $\boldsymbol{R}^n$. We utilize variational method and critical point theory to establish our mainresults.